A kind of antistatic PP composite material based on carbon black and preparation method thereof
By introducing synergistic agents and conductive carbon black into the polypropylene composite material to form a uniform conductive network, the problems of insufficient temperature resistance and poor antistatic effect in the polypropylene composite material are solved, and efficient antistatic properties and good mechanical properties are achieved.
Patent Information
- Application Number
- CN202510208348.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-02-25
AI Technical Summary
Existing polypropylene (PP) composite materials are prone to static electricity in the fields of electronic components and food packaging, resulting in problems such as product adhesion, dust adsorption and printing defects. The existing antistatic agents have problems such as insufficient temperature resistance, strong mobility, high safety risks and poor antistatic effect.
Using carbon black-based antistatic PP composite material, the amount of conductive carbon black is reduced by introducing a synergistic agent, the uniform dispersion of carbon black in the composite material and the formation of conductive networks is improved, and the antistatic ability of the composite material is improved.
The antistatic properties of polypropylene composite materials are improved at a lower amount of conductive carbon black, reducing the problem of mechanical properties deterioration caused by carbon black, while maintaining good compatibility and mechanical properties of the composite materials.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer composite materials, and in particular, relates to an antistatic PP composite material based on carbon black and a preparation method thereof. Background Art
[0002] Polypropylene (PP) is a commonly used thermoplastic with good mechanical properties, chemical stability and heat resistance. However, polypropylene is prone to static electricity, which can cause problems such as object adhesion, dust adsorption, and printing defects. The static electricity problem is particularly prominent in the fields of electronic components and food packaging.
[0003] At present, the main method to improve the antistatic performance of polypropylene is to add antistatic agents. Existing antistatic agents can be divided into organic antistatic agents and inorganic antistatic agents according to their chemical composition. Among them, organic antistatic agents are generally more compatible with polypropylene matrix and can achieve excellent antistatic effects at lower dosages. However, they have insufficient temperature resistance and are easy to migrate in products, making it difficult to provide stable and long-term antistatic effects. In addition, there are certain safety risks, and their application in many products is restricted. In comparison, inorganic antistatic agents have stable heat resistance, are not easy to migrate, and have almost no leakage risks. However, their antistatic effects are not good. Sufficient amount is needed to form a conductive network that is in contact and connected with each other to have an antistatic effect. However, in polypropylene composite materials, these inorganic antistatic agents are difficult to disperse evenly, forming internal defects, which leads to a sharp deterioration in the mechanical properties of the composite materials. In the prior art, the compatibility of inorganic antistatic agents is improved to a certain extent through surface treatment of inorganic antistatic agents, such as common coupling treatment. However, this coupling material forms a physical partition, which reduces the conductivity between the inorganic antistatic agents, resulting in a decrease in the antistatic effect. The dispersion and antistatic effect can only be adjusted according to demand, and it is difficult to improve them synergistically. Summary of the invention
[0004] In order to solve the technical problems mentioned in the background technology, the purpose of the present invention is to provide an antistatic PP composite material based on carbon black and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A carbon black-based antistatic PP composite material, comprising the following components: 5.5-8.2wt% of conductive carbon black, 4.5-5.5wt% of a synergist, 1.6-2.1wt% of a compatibilizer, 0.15-0.2wt% of a lubricant, 0.07-0.09wt% of an antioxidant, and the remainder being PP masterbatch.
[0007] The synergist is prepared by the following method:
[0008] Step A1: glycerol dimethacrylate, 1,3-propane sultone, triethylamine and anhydrous tetrahydrofuran are mixed and added, the temperature is raised to 55-65° C., and the mixture is stirred at 120-180 rpm for 4-5 hours. After the reaction is completed, tetrahydrofuran is removed by rotary evaporation to obtain monomer a;
[0009] Furthermore, the feed ratio of glyceryl dimethacrylate, 1,3-propane sultone, triethylamine and anhydrous tetrahydrofuran is 0.1 mol: 0.1 mol: 4-6 mL: 40-55 mL, and 1,3-propane sultone reacts with the hydroxyl group in glyceryl dimethacrylate to introduce a sulfonated structure.
[0010] Step A2: premix p-aminodiphenylamine, acetone and hydrochloric acid, control the temperature in an ice-water bath to no more than 10°C, slowly add ammonium persulfate solution and stir to react for 3.5-4h, remove acetone by rotary evaporation, add ammonia water to the substrate to adjust the pH value to 8, filter and redissolve with carbon tetrachloride, then add methacrylic anhydride, raise the temperature to 60-70°C and react for 3-4h, remove carbon tetrachloride by rotary evaporation after the reaction is completed, add water to wash, separate the liquids and vacuum dry to obtain monomer b;
[0011] Furthermore, the feed ratio of p-aminodiphenylamine, methacrylic anhydride, ammonium persulfate, hydrochloric acid, acetone and carbon tetrachloride is 0.1 mol: 45-60 mmol: 0.7-0.9 g: 15-22 mL: 65-85 mL: 40-55 mL. Under the initiation of hydrochloric acid and ammonium persulfate, p-aminodiphenylamine self-polymerizes to form a single-terminal amino group aniline polymer, and then the highly active methacrylic anhydride reacts with the terminal amino group to introduce a terminal acrylamide structure.
[0012] Step A3: Mix monomer b, styrene, octene, azobisisobutyronitrile and dimethylformamide, heat to 60-70°C, stir and react for 5-7h, then add monomer a, continue to heat to 90-100°C and react for 2-3h, add acetic acid solution and wash after the reaction, filter, wash and dry to obtain a synergist;
[0013] Furthermore, the feed ratio of monomer b, styrene, octene, monomer a, azobisisobutyronitrile and dimethylformamide is 20g:30-45mmol:55-80mmol:15-20mmol:0.13-0.18g:85-110mL. Under the initiation of azobisisobutyronitrile, monomer b, styrene and octene are prepolymerized, and then monomer a is block copolymerized to form a copolymer with a polyolefin as the main chain.
[0014] Furthermore, the conductive carbon black is selected from nano-sized powders, and small-sized powders are easy to interact with the synergist and be evenly dispersed.
[0015] Furthermore, the compatibilizer is selected from maleic anhydride grafted polypropylene to improve the compatibility between the synergist and the conductive carbon black and the PP masterbatch.
[0016] Furthermore, the lubricant is compounded from polypropylene wax and calcium stearate, has good internal and external lubrication effects, and is beneficial to the molding of the composite material.
[0017] A method for preparing an antistatic PP composite material based on carbon black comprises the following steps: uniformly mixing the raw materials of each component with a high-speed mixer, plasticizing and mixing the mixture at 230-240° C., extruding and stretching, cooling and pelletizing to obtain the antistatic PP composite material.
[0018] Beneficial effects of the present invention:
[0019] The invention is based on a carbon black antistatic composite system, and introduces a synergist for blending, thereby reducing the amount of conductive carbon black added to a certain extent, and alleviating the problem of deterioration of mechanical properties of composite materials caused by carbon black as a discontinuous defect; the synergist is prepared by the reaction of 1,3-propane sultone with a hydroxyl group in dimethacrylate glycerol, and a sulfonation structure is grafted into the dimethacrylate glycerol molecule to prepare a monomer a, and a single-terminal amino group aniline polymer is formed by self-polymerization of p-aminodiphenylamine, and then a terminal amino group is reacted with highly active methacrylic anhydride to form a terminal acrylamide structure capping to prepare a monomer b, and the monomer b, styrene and octene are prepolymerized, and then the monomer a is block copolymerized to obtain the synergist; the synergist is a macromolecular polymer, the main chain of which is a polyolefin chain, the side chain of which is an alkyl branch introduced from the octene block, and the monomer b is a styrene and octene. It has good compatibility with the polypropylene matrix and can be evenly dispersed during the blending process, with little effect on the mechanical properties of the matrix. Monomer a introduces a small amount of polar groups into the chain, which has a high affinity with conductive carbon black. In addition, the sulfonic acid groups introduced by monomer a are easy to form hydrogen bonds with the oxygen-containing groups on the surface of the conductive carbon black, so that the conductive carbon black is evenly dispersed with the block chain segments of monomer a as a template, which makes it easier to form a conductive path, so that static electricity can be released and discharged in time. At the same time, the evenly dispersed conductive carbon black particles are not easy to form internal defects, and have little effect on the mechanical properties of the polypropylene matrix. In addition, the aniline polymer of the synergist side chain has good conductivity, which forms a comb-shaped structure with the main chain, forms a bridging effect between the conductive carbon black particles, and forms an organic-inorganic conductive network, which further enhances the antistatic ability of the composite material. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Example 1, preparation of an antistatic PP composite material based on carbon black, specifically as follows:
[0022] (1) Preparation of synergists
[0023] Step A1: Take dimethacrylate glycerol, 1,3-propane sultone, triethylamine and anhydrous tetrahydrofuran, mix and feed, heat to 55°C, and stir at 120rpm to react for 5h, wherein the feed ratio of dimethacrylate glycerol, 1,3-propane sultone, triethylamine and anhydrous tetrahydrofuran is 0.1mol:0.1mol:4mL:40mL. After the reaction, remove tetrahydrofuran by rotary evaporation to obtain monomer a.
[0024] Step A2: pre-mix p-aminodiphenylamine, acetone and hydrochloric acid, control the temperature at 0°C in an ice-water bath, slowly add ammonium persulfate solution and stir to react for 4 hours, remove acetone by rotary evaporation, add ammonia water to the substrate to adjust the pH value to 8, wash and filter, redissolve with carbon tetrachloride, add methacrylic anhydride, heat to 60°C and react for 4 hours, wherein the feed ratio of p-aminodiphenylamine, methacrylic anhydride, ammonium persulfate, hydrochloric acid, acetone and carbon tetrachloride is 0.1 mol: 45 mmol: 0.7 g: 15 mL: 65 mL: 40 mL, the concentration of hydrochloric acid is 0.5 mol / L, the ammonium persulfate solution is a saturated aqueous solution at room temperature, and after the reaction, remove carbon tetrachloride by rotary evaporation, wash with water, separate the liquids and dry in vacuo to obtain monomer b.
[0025] Step A3: Take monomer b, styrene, octene, azobisisobutyronitrile and dimethylformamide, mix and feed, heat to 60°C, stir and react for 7 hours, then add monomer a, continue to heat to 90°C and react for 3 hours, wherein the feed ratio of monomer b, styrene, octene, monomer a, azobisisobutyronitrile and dimethylformamide is 20g:30mmol:80mmol:15mmol:0.13g:85mL. After the reaction is completed, add 10% acetic acid solution with a volume fraction to mix, filter, wash and dry to obtain a synergist.
[0026] (2) Preparation of antistatic PP composite materials
[0027] Ingredients: 5.5wt% conductive carbon black, selected from 3030B nano-conductive carbon black powder of Mitsubishi Chemical Group; 4.5wt% synergist, prepared in this embodiment; 1.6wt% compatibilizer, selected from A1028 maleic anhydride grafted polypropylene of Shenzhen Paste New Material Technology Co., Ltd.; 0.15wt% lubricant, selected from PP-200 polypropylene wax and industrial-grade calcium stearate of Shanghai Huayi Chemical Additive Co., Ltd. in an equal weight ratio; 0.07wt% antioxidant, selected from antioxidant 1010 and antioxidant 168 in an equal weight ratio; the remainder is PP masterbatch, selected from SP179 raw material of Qilu Petrochemical.
[0028] Mixing: Add the raw materials of each component into a high-speed mixer, mix at 600 rpm for 15 minutes, plasticize and mix the mixture at 230°C, extrude and stretch, cool and pelletize to obtain an antistatic PP composite material.
[0029] Example 2, preparation of an antistatic PP composite material based on carbon black, as follows:
[0030] (1) Preparation of synergists
[0031] Step A1: Take dimethacrylate glycerol, 1,3-propane sultone, triethylamine and anhydrous tetrahydrofuran, mix them and feed them, heat them to 65°C, and stir them at 180rpm for 4 hours, wherein the feed ratio of dimethacrylate glycerol, 1,3-propane sultone, triethylamine and anhydrous tetrahydrofuran is 0.1 mol: 0.1 mol: 6 mL: 55 mL. After the reaction, remove tetrahydrofuran by rotary evaporation to obtain monomer a.
[0032] Step A2: pre-mix p-aminodiphenylamine, acetone and hydrochloric acid, control the temperature at 10°C in an ice-water bath, slowly add ammonium persulfate solution and stir to react for 3.5 hours, remove acetone by rotary evaporation, add ammonia water to the substrate to adjust the pH value to 8, wash and filter, redissolve with carbon tetrachloride, add methacrylic anhydride, heat to 70°C and react for 3 hours, wherein the feed ratio of p-aminodiphenylamine, methacrylic anhydride, ammonium persulfate, hydrochloric acid, acetone and carbon tetrachloride is 0.1 mol: 60 mmol: 0.9 g: 22 mL: 85 mL: 55 mL, the concentration of hydrochloric acid is 0.5 mol / L, the ammonium persulfate solution is a saturated aqueous solution at room temperature, and after the reaction, remove carbon tetrachloride by rotary evaporation, wash with water, separate the liquids and dry in vacuo to obtain monomer b.
[0033] Step A3: Take monomer b, styrene, octene, azobisisobutyronitrile and dimethylformamide, mix and feed, heat to 70°C, stir and react for 5 hours, then add monomer a, continue to heat to 100°C and react for 2 hours, wherein the feed ratio of monomer b, styrene, octene, monomer a, azobisisobutyronitrile and dimethylformamide is 20g:45mmol:55mmol:20mmol:0.18g:110mL, after the reaction is completed, add 10% by volume acetic acid solution to wash, filter, wash and dry to obtain a synergist.
[0034] (2) Preparation of antistatic PP composite materials
[0035] Ingredients: According to the weight percentage, 8.2wt% of conductive carbon black is selected from 3030B nano-grade conductive carbon black powder of Mitsubishi Chemical Group; 5.5wt% of synergist is self-made in this embodiment; 2.1wt% of compatibilizer is selected from A1028 maleic anhydride grafted polypropylene of Shenzhen Paste New Material Technology Co., Ltd.; 0.2wt% of lubricant is selected from PP-200 polypropylene wax and industrial grade calcium stearate of Shanghai Huayi Chemical Additive Co., Ltd. in an equal weight ratio; 0.09wt% of antioxidant is selected from antioxidant 1010 and antioxidant 168 in an equal weight ratio; the remainder is PP masterbatch, selected from SP179 raw material of Qilu Petrochemical.
[0036] Mixing: Add the raw materials of each component into a high-speed mixer, mix at 600 rpm for 15 minutes, plasticize and mix the mixture at 240°C, extrude and stretch, cool and pelletize to obtain an antistatic PP composite material.
[0037] Example 3, preparation of an antistatic PP composite material based on carbon black, as follows:
[0038] (1) Preparation of synergists
[0039] Step A1: Take dimethacrylate glycerol, 1,3-propane sultone, triethylamine and anhydrous tetrahydrofuran, mix and feed, heat to 60°C, and stir at 180rpm to react for 4.5h, wherein the feed ratio of dimethacrylate glycerol, 1,3-propane sultone, triethylamine and anhydrous tetrahydrofuran is 0.1mol:0.1mol:5mL:50mL. After the reaction, remove tetrahydrofuran by rotary evaporation to obtain monomer a.
[0040] Step A2: pre-mix p-aminodiphenylamine, acetone and hydrochloric acid, control the temperature at 5°C in an ice-water bath, slowly add ammonium persulfate solution and stir to react for 3.8h, remove acetone by rotary evaporation, add ammonia water to the substrate to adjust the pH value to 8, wash and filter, redissolve with carbon tetrachloride, add methacrylic anhydride, heat to 65°C and react for 3.2h, wherein the feed ratio of p-aminodiphenylamine, methacrylic anhydride, ammonium persulfate, hydrochloric acid, acetone and carbon tetrachloride is 0.1mol:50mmol:0.8g:18mL:75mL:50mL, the concentration of hydrochloric acid is 0.5mol / L, the ammonium persulfate solution is a saturated aqueous solution at room temperature, and after the reaction, remove carbon tetrachloride by rotary evaporation, wash with water, separate the liquids and dry in vacuo to obtain monomer b.
[0041] Step A3: Take monomer b, styrene, octene, azobisisobutyronitrile and dimethylformamide, mix and feed, heat to 62°C, stir and react for 6.5h, then add monomer a, continue to heat to 95°C and react for 2.4h, wherein the feed ratio of monomer b, styrene, octene, monomer a, azobisisobutyronitrile and dimethylformamide is 20g:35mmol:70mmol:17mmol:0.16g:100mL, after the reaction is completed, add 10% by volume acetic acid solution to wash, filter, wash and dry to obtain a synergist.
[0042] (2) Preparation of antistatic PP composite materials
[0043] Ingredients: According to the weight percentage, the conductive carbon black is 7.5wt%, selected from the 3030B nano-grade conductive carbon black powder of Mitsubishi Chemical Group; the synergist is 5wt%, which is prepared in this embodiment; the compatibilizer is 1.8wt%, selected from the A1028 maleic anhydride grafted polypropylene of Shenzhen Paste New Material Technology Co., Ltd.; the lubricant is 0.17wt%, selected from the PP-200 polypropylene wax and industrial-grade calcium stearate of Shanghai Huayi Chemical Additive Co., Ltd. in an equal weight ratio; the antioxidant is 0.08wt%, which is compounded by antioxidant 1010 and antioxidant 168 in an equal weight ratio; the balance is PP masterbatch, selected from the SP179 raw material of Qilu Petrochemical.
[0044] Mixing: Add the raw materials of each component into a high-speed mixer, mix at 600 rpm for 15 minutes, plasticize and mix the mixture at 230°C, extrude and stretch, cool and pelletize to obtain an antistatic PP composite material.
[0045] Comparative Example 1: This comparative example refers to Example 3, except that no synergist is added, and the balance is supplemented by PP masterbatch to 100%, and the rest of the implementation process is exactly the same.
[0046] Comparative Example 2: This comparative example refers to Example 3, except that no synergist is added, the conductive carbon black addition amount is 12.5wt%, and the balance is supplemented by PP masterbatch to 100%, and the rest of the implementation process is exactly the same.
[0047] In Comparative Example 3, coupled conductive carbon black is used to replace the conductive carbon black in Comparative Example 2, and the balance is supplemented by PP masterbatch to 100%, and the rest of the implementation process is exactly the same; wherein, the preparation method of the coupled conductive carbon black is: premixing butyltrimethoxysilane and 50% by volume ethanol aqueous solution, adjusting the pH value to 3 with formic acid, stirring and hydrolyzing at room temperature for 1 hour, adding conductive carbon black and mixing at 240rpm for 30min, and then neutralizing with ammonia water, wherein the feed ratio of conductive carbon black, butyltrimethoxysilane and ethanol aqueous solution is 10g:1.5mL:35mL, standing to take the precipitate, washing and drying to obtain coupled conductive carbon black.
[0048] Comparative Example 4: This comparative example refers to Example 3, except that the synergist is replaced with the same amount of polyquaternary ammonium salt antistatic SN, and the rest of the implementation process is exactly the same.
[0049] Samples were taken from the composite material prepared as above, and were hot pressed into sheets at 240°C and 10MPa using a flat vulcanizer. The samples were subjected to tensile tests according to GB / T 1040.2-2022 and surface resistivity tests according to IEC 61340 5-1-2016. The specific test results are shown in Table 1:
[0050] Table 1
[0051]
[0052] It can be seen from the test results in Table 1 that the composite material prepared in the embodiment has good comprehensive mechanical properties, low surface resistivity and excellent antistatic effect.
[0053] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0054] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. An antistatic PP composite material based on carbon black, characterized in that: The components of the antistatic PP composite material are as follows: 5.5-8.2wt% of conductive carbon black, 4.5-5.5wt% of synergist, 1.6-2.1wt% of compatibilizer, 0.15-0.2wt% of lubricant and 0.07-0.09wt% of antioxidant, and the balance is PP masterbatch; The synergist is prepared by the following method: Step A1: Mix dimethacrylate glycerol, 1,3-propane sultone, triethylamine and anhydrous tetrahydrofuran, heat to 55-65° C., stir and react for 4-5 hours to obtain monomer a; Step A2: pre-mix p-aminodiphenylamine, acetone and hydrochloric acid, control the temperature in an ice-water bath to no more than 10°C, slowly add ammonium persulfate solution and stir to react for 3.5-4h, remove acetone by rotary evaporation, add ammonia water to the substrate to adjust the pH value to 8, filter and redissolve with carbon tetrachloride, then add methacrylic anhydride, raise the temperature to 60-70°C and react for 3-4h to obtain monomer b; Step A3: Mix monomer b, styrene, octene, azobisisobutyronitrile and dimethylformamide, heat to 60-70°C, stir and react for 5-7h, then add monomer a, continue to heat to 90-100°C and react for 2-3h to obtain a synergist.
2. The antistatic PP composite material based on carbon black according to claim 1, characterized in that: The feed ratio of dimethacrylate glycerol, 1,3-propane sultone, triethylamine and anhydrous tetrahydrofuran is 0.1 mol: 0.1 mol: 4-6 mL: 40-55 mL.
3. The antistatic PP composite material based on carbon black according to claim 1, characterized in that: The feed ratio of p-aminodiphenylamine, methacrylic anhydride, ammonium persulfate, hydrochloric acid, acetone and carbon tetrachloride is 0.1 mol: 45-60 mmol: 0.7-0.9 g: 15-22 mL: 65-85 mL: 40-55 mL.
4. The antistatic PP composite material based on carbon black according to any one of claims 2 to 3, characterized in that: The feed ratio of monomer b, styrene, octene, monomer a, azobisisobutyronitrile and dimethylformamide is 20g:30-45mmol:55-80mmol:15-20mmol:0.13-0.18g:85-110mL.
5. The antistatic PP composite material based on carbon black according to claim 1, characterized in that: Conductive carbon black is nano-scale powder.
6. The antistatic PP composite material based on carbon black according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polypropylene.
7. The antistatic PP composite material based on carbon black according to claim 1, characterized in that: The lubricant is compounded from polypropylene wax and calcium stearate.
8. The method for preparing an antistatic PP composite material based on carbon black according to claim 1, characterized in that: Specifically, the raw materials of each component are mixed evenly by a high-speed mixer, the mixture is plasticized and mixed at 230-240° C., extruded and drawn, cooled and pelletized to obtain an antistatic PP composite material.
Citation Information
Patent Citations
Polypropylene composition, reinforced flame retardant antistatic polypropylene and preparation method thereof, and product
CN108864562A
Filter material cleaning agent as well as preparation method and application thereof
CN115491266A